Ramp thickness and ion heating in 1D simulations of laminar quasi-perpendicular shocks - Wilkinson, William P. (Geophysical research letters, 1997)
One‐dimensional hybrid simulations are used to investigate the effect of the shock ramp's width on the heating of the transmitted ions at low Mach number nearly perpendicular shocks. The suitability of the hybrid code for such a study is established by considering the correlation between precursor wavelength and ramp thickness as a function of θBn, the angle between the upstream magnetic field and upstream‐pointing shock normal. The simulated shocks are found to preserve their dispersive character at geometries close to perpendicular, becoming rapidly narrower as θBn approaches 90°. The effect of shock thickness on the transmitted ions is examined by comparing their heating at three shocks with θBn = 83°, 86° and 88°, respectively, which are successively thinner by a factor of 2. The results are discussed in the light of recent theoretical studies on the subject.